Penyuluhan Pencegahan Stunting dan Pengukuran Antropometri di Posyandu Cempaka RW “A” Kelurahan Kemirimuka, Kecamatan Beji, Depok-Jawa Barat - Fri Rahmawati; Maria Bintang; Albert Jackson Yang; Elferida Sormin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Malnutrition is still a major problem in infants and children globally. Data from the World Health Organization (WHO) for 2020 shows that the prevalence of stunting globally is in the high category because it is between 20% - 30%. Indonesia is the sixth country in the South-East Asia region with 36,4% of stunting cases. Incidence of stunting occurs due to chronic malnutrition in children after birth. Malnutrition can occur as a result of a child after birth getting insufficient food or breast milk for growth. Therefore it is necessary to do various ways to prevent the incidence of stunting in the community, one of the efforts is through counseling to prevent stunting by using herbal ingredients to increase breast milk and monitoring the nutritional status of toddlers through anthropometric measurements. Community service activities carried out included counseling on stunting prevention and anthropometric measurements at Posyandu Cempaka RW “A”, Kemirimuka Village, Beji District, Depok City, JABAR. Based on the results of anthropometric measurements, based on weight and height, it is known that most of the respondents who came to Community servicetivities were normally and excess nutritious, but there were respondents who were stunted.